Impulsive control for uncertain systems with time-invariant delay and non-linear disturbance. (11th November 2008) - Ju, H.W.; Cui, B.T.
In this paper, robust stability and robust exponential stability for uncertain systems with time delay and non-linear disturbance are investigated. By employing the method of Lyapunov function and linear matrix inequality approach, several stability criteria are established and the stable region is also estimated. Our results show that these classes of system can be stabilised by impulses. These obtained results are then applied to the design of impulsive controller. An example and its simulation are also given to illustrate our results.